Viable strategies for enhancing performance in ball sports by mitigating mental fatigue: a systematic review - Pan, Xiaoyang; Soh, Kim Geok; Soh, Kim Lam (Public Library of Science (PLoS), 2024)
Ball sports demand precise control of body and ball while executing tactics and team coordination, which leads to cognitive depletion and mental fatigue. The detrimental effects of mental fatigue on physical, technical, cognitive, and tactical performance in ball sports are evident, highlighting the need for effective management of mental fatigue as a crucial component of modern sports science. This review aims to systematically study and integrate existing experiments on mental fatigue recovery interventions to identify viable strategies for mitigating its impacts. Following PRISMA guidelines, electronic databases including Web of Science, PubMed, SPORTDiscus, and Scopus were used for literature screening. Studies that induced mental fatigue followed by interventions aimed at mental fatigue recovery were included in this review, resulting in 6 articles primarily focused on basketball, soccer, and golf. Short-term interventions such as music listening, mindfulness training, self-talk, and natural visual stimuli have been shown as effective strategies to alleviate mental fatigue and enhance technical and cognitive performance in ball sports. However, their practical application in real-game environments requires further research and validation. Additionally, future research should explore defensive skills and tactical performance as viable directions for study. © 2024 Pan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.